2019
DOI: 10.1037/ocp0000132
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness training improves employee well-being: A randomized controlled trial.

Abstract: Organizations are turning toward behavioral interventions with the aim of improving employee wellbeing and job performance. Mindfulness training has been suggested as one type of intervention that can achieve these goals, but few active treatment randomized controlled trials have been conducted. We conducted a randomized controlled trial among employees of a midwestern marketing firm (n ϭ 60) that compared the effects of 6-week mindfulness training program with that of a half-day mindfulness training seminar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…Since we reported a significant decrease in perceived stress in the current sample this explanation does not account for our findings. Given that several organizational mindfulnessbased interventions do not report employing any mindfulness assessment (Davidson et al, 2003;Bazarko et al, 2013;Shonin et al, 2014;Chin et al, 2019b;Slutsky et al, 2019) further research with organizational interventions is required to explore how the different facets of mindfulness are affected by different interventions. In contrast to the findings of Querstret et al (2018), we reported significant increases on the non-reacting to inner experience facet of the FFMQ-SF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since we reported a significant decrease in perceived stress in the current sample this explanation does not account for our findings. Given that several organizational mindfulnessbased interventions do not report employing any mindfulness assessment (Davidson et al, 2003;Bazarko et al, 2013;Shonin et al, 2014;Chin et al, 2019b;Slutsky et al, 2019) further research with organizational interventions is required to explore how the different facets of mindfulness are affected by different interventions. In contrast to the findings of Querstret et al (2018), we reported significant increases on the non-reacting to inner experience facet of the FFMQ-SF.…”
Section: Discussionmentioning
confidence: 99%
“…Querstret et al (2018) used 4 of the 5 facets of the FFMQ-SF (the observing facet was excluded due to prior research by Baer et al (2006Baer et al ( , 2008 showing that observing didn't load onto a single mindfulness construct and did not show changes in meditation-naïve participants), and reported that the non-reactivity facet did not change following the interventions. Finally, several other interventions did not report the use of any mindfulness assessment as an outcome measure (Davidson et al, 2003;Bazarko et al, 2013;Chin et al, 2019b;Slutsky et al, 2019), preventing conclusions about the effects of those intervention on trait mindfulness to be drawn. In the present research we elected to employ the FFMQ-SF, and hypothesized that the mindfulness facets would increase following the mindfulness intervention relative to a randomized waitlist control group (H1).…”
Section: Mindfulness Interventions and Trait Mindfulnessmentioning
confidence: 99%
See 2 more Smart Citations
“…The systematic review by Donaldson-Feilder et al [28] reported positive effects on the well-being, resilience and leadership capability of leaders/managers. Slutsky et al [29] conducted a randomised controlled trial (RCT) and…”
Section: Individual-focused Secondary Health Intervention: Mbsrmentioning
confidence: 99%